Towards developing walking assistants for the visually impaired people - Kamal, Md. Mostafa; Bayazid, Abu Ibne; Sadi, Muhammad Sheikh; Islam, Md. Milon; Hasan, Nazmul (2017 IEEE Region 10 Humanitarian Technology Conference (R10-HTC), 2017)
Blindness is the condition of lacking discernment because of physiological or neurological components. Different techniques have been established to define the degree of vision misfortune and visual deficiency. The problems that visually impaired people are facing are that they cannot avoid the objects around them while moving, so accident may occur. Various researches have been conducted to minimize the sufferings of the visually impaired people. But it does not reach to the optimized level. The contribution of this paper is to investigate a solution for the visually impaired people. This paper targets to provide a solution that helps blind to avoid obstacles around them without holding any sticks or other heavy things. The system calculated the smoothness of the surface both for the daylight and dark using RGB data through microcontroller and smartphone. The highest smoothness of the surface is achieved by the system is 96.341% and 98.683% for the day-night and dark respectively. It designs and develops a system which is consisting of small, wearable, lightweight, low-cost spectacle for the blind by which they can get assistance to walk easily and detect obstacles around them.